2013
DOI: 10.1080/13678868.2013.771868
|View full text |Cite
|
Sign up to set email alerts
|

A Trojan Horse? The implications of managerial coaching for leadership theory

Abstract: This article examines the behaviours associated with managerial coaching and assesses the implications for leadership theory. Survey data from 521 line managers are analysed to: (i) identify the behaviours associated with managerial coaching, (ii) examine factors that affect the propensity of managers to undertake coaching and (iii) discuss the implications of the manager as coach role for leadership theory and practice. First, the analysis indicates that workplace coaching is distinct from specialized coachin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(76 citation statements)
references
References 69 publications
1
73
1
1
Order By: Relevance
“…Schalock & Alonso (2012) refer to four leadership roles needed in disability organisations: (1) mentoring and directing, (2) coaching and instructing, (3) inspiring and empowering and (4) collaborating and partnering. Elements of leadership such as modelling and coaching have long been recognised as important techniques for shaping skills and behaviour in many fields of health and human services (Cherniss 1980;Werner & DeSimone 2006;Anderson 2013) as well as intellectual disability services (Schalock et al 2008;Ashman et al 2010). Following Cherniss's conceptualisation, Mansell & Beadle-Brown (2012) described the model of practice leadership needed to deliver high quality support in intellectual disability services as involving skilled professional advice and assistance as well as administrative control, and an educational and developmental role rather than simply providing direction.…”
Section: Defining Practice Leadershipmentioning
confidence: 99%
See 1 more Smart Citation
“…Schalock & Alonso (2012) refer to four leadership roles needed in disability organisations: (1) mentoring and directing, (2) coaching and instructing, (3) inspiring and empowering and (4) collaborating and partnering. Elements of leadership such as modelling and coaching have long been recognised as important techniques for shaping skills and behaviour in many fields of health and human services (Cherniss 1980;Werner & DeSimone 2006;Anderson 2013) as well as intellectual disability services (Schalock et al 2008;Ashman et al 2010). Following Cherniss's conceptualisation, Mansell & Beadle-Brown (2012) described the model of practice leadership needed to deliver high quality support in intellectual disability services as involving skilled professional advice and assistance as well as administrative control, and an educational and developmental role rather than simply providing direction.…”
Section: Defining Practice Leadershipmentioning
confidence: 99%
“…Schalock & Alonso () refer to four leadership roles needed in disability organisations: (1) mentoring and directing, (2) coaching and instructing, (3) inspiring and empowering and (4) collaborating and partnering. Elements of leadership such as modelling and coaching have long been recognised as important techniques for shaping skills and behaviour in many fields of health and human services (Cherniss ; Werner & DeSimone ; Anderson ) as well as intellectual disability services (Schalock et al . ; Ashman et al ).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, informal coaching occurs during everyday workplace conversations Á the few minutes snatched in the corridor in the midst of a busy project for a short highly focused coaching conversation (Greene & Grant, 2003) Á in which coaching techniques are used more implicitly. This kind of informal coaching accounts for most of the coaching conversations that managers have (Anderson, 2013). In addition, we have found that making clear distinctions between skills, performance and developmental coaching helps participants gain greater clarity on the type of coaching that is required in any specific situation (Standards Australia, 2011).…”
Section: Program Contentmentioning
confidence: 99%
“…For instance, Bass and Avolio's (1994) transformational leadership style is essentially about motivating followers to look beyond their own self-interest toward the achievement of team-related goals (Bormann and Rowold, 2018). In contrast, leaders' coaching behaviors refer to one-on-one interactions between a leader and an employee aimed at stimulating individual growth (Anderson, 2013) and may therefore be more suitable for addressing personal and professional developmental goals (Kunst et al, 2018).…”
Section: Theory and Hypotheses Defining Coaching-based Leadershipmentioning
confidence: 99%